2013
DOI: 10.1007/s11605-013-2198-1
|View full text |Cite
|
Sign up to set email alerts
|

Fistulotomy in the Tertiary Setting can Achieve High Rates of Fistula Cure with an Acceptable Risk of Deterioration in Continence

Abstract: We have shown that it is safe and reasonable to offer fistulotomy to appropriate patients despite previous surgery and within the tertiary setting. By so doing, a very high rate of healing can be achieved in patients who have previously failed. The additional risk of impairment of continence is around one in five, and in the majority will represent only minor incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 16 publications
1
30
0
1
Order By: Relevance
“…The healing rate of this technique ranges from 93%-100%. Because the sphincters are inevitably transected in this procedure, minor incontinence is reported in 11.5%-20% of cases [6][7][8][9]. For complex fistulas, however, treatment is more difficult and carries a higher recurrence rate and greater potential of external sphincter damage [10].…”
Section: Discussionmentioning
confidence: 99%
“…The healing rate of this technique ranges from 93%-100%. Because the sphincters are inevitably transected in this procedure, minor incontinence is reported in 11.5%-20% of cases [6][7][8][9]. For complex fistulas, however, treatment is more difficult and carries a higher recurrence rate and greater potential of external sphincter damage [10].…”
Section: Discussionmentioning
confidence: 99%
“…24 Another series by the same authors reported results of 50 patients, and reported a recurrence rate of 7%, with minor control problems in 40%. 25 Primary fistulotomy with end-to-end primary sphincteroplasty is another treatment option. In 2013, Ratto et al reported on this technique for 72 patients with complex anal fistula of cryptoglandular origin.…”
Section: Fistulotomymentioning
confidence: 99%
“…Fistulectomy is usually recommended for low anal fistulas, as the success rate is high with this procedure, and with minimal incontinence. The success rates can be as high as 93 to 100 % in experienced hands [28,29]. The incontinence is usually minor and can range from 11.5 to 20 %.…”
Section: Fistulectomymentioning
confidence: 98%